Faktor Yang Mempengaruhi Keberhasilan Pemerintah Kota Malang Dalam Menangani Tingkat Kriminalitas - Aminkun Imam Rafii (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Crime is any action or something that is done by an individual, group or community that violates the law or an act of crime, which disturbs the balance or social stability in society. The economic crisis, poverty, unemployment, and social inequality are some of the factors that often trigger criminal acts, especially in big cities including Malang City. This study aims to examine how strong the level of education, poverty, and unemployment can influence crime. The data used in this study is secondary data obtained from the official website of the Central Bureau of Statistics for the City of Malang in 2022. The data that has been collected is then analyzed using regression analysis. The results of this study indicate that poverty and unemployment are important factors either partially or simultaneously to control and prevent crime rates. However, in this study it was found that the level of education in Malang City did not significantly influence the crime rate. Referring to these results, controlling crime in Malang City can be more focused on reducing poverty and unemployment. These two factors have a major contribution to the crime model in Malang City (R2=93%).